1997
DOI: 10.2307/3587834
|View full text |Cite
|
Sign up to set email alerts
|

The Negotiation of Teachers' Sociocultural Identities and Practices in Postsecondary EFL Classrooms

Abstract: This article explores the complex interrelationships between language and culture, between teachers' sociocultural identities and teaching practices, and between their explicit discussions of culture and implicit modes of cultural transmission in their classes. A 6‐month ethnographic study examined how teachers deal with institutional and curricular expectations regarding their teaching of (North American) culture in their EFL classrooms in a postsecondary institution in Japan. The study also explored the teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
203
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 350 publications
(241 citation statements)
references
References 84 publications
7
203
0
5
Order By: Relevance
“…First, the teachers in our study used their personal experiences, often cross-cultural ones, and their understandings of these experiences to make sense of pedagogical content and concepts, similar to previous studies (Duff & Uchida, 1997;Menard-Warwick, 2008). Sometimes, this reference to personal experiences and understandings was prompted by the instructors; at other times, the teacher participants chose to connect with their experiences and understandings while processing new concepts introduced in this PD course.…”
Section: Teachers Made Two-way Connections Between Cultural Identimentioning
confidence: 99%
See 4 more Smart Citations
“…First, the teachers in our study used their personal experiences, often cross-cultural ones, and their understandings of these experiences to make sense of pedagogical content and concepts, similar to previous studies (Duff & Uchida, 1997;Menard-Warwick, 2008). Sometimes, this reference to personal experiences and understandings was prompted by the instructors; at other times, the teacher participants chose to connect with their experiences and understandings while processing new concepts introduced in this PD course.…”
Section: Teachers Made Two-way Connections Between Cultural Identimentioning
confidence: 99%
“…The process of doing this complex cultural and social identity work was analyzed by Duff and Uchida (1997), who examined how four English as foreign language (EFL) teachers' sociocultural identities interacted with their institutional and interpersonal environments in Japan. Viewing identities as "co-constructed, negotiated, and transformed on an ongoing basis by means of language" (p. 452), this ethnographic case study found that the teachers' sociocultural identities developed along two dimensions: a biographical/professional one (e.g., past learning and teaching experiences) and a contextual one (e.g., the local classroom culture).…”
Section: A Cultural Identitiesmentioning
confidence: 99%
See 3 more Smart Citations